Bawa and beyond : reading Sri Lanka's tropical modern architecture - Jazeel, Tariq; International Centre for Ethnic Studies (Colombo : International Centre for Ethnic Studies, 2006)
Address by the speaker at International Centre for Ethnic Studies.
Includes bibliographical references (p. 30-32).
Keywords: Bawa, Geoffrey, -- 1919-2003 -- Criticism and interpretation; Architecture -- Sri Lanka -- History -- 20th century; Architecture, Tropical -- Sri Lanka